Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Trifting Di Noah Fashion Medan - Girsang, Andrea Yunika; Siregar, Dahrul; Meutia, Riza Fany; Trg, Eka Dewi Setia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the effect of product quality, price, and promotion on consumer purchase decisions at Noah Fashion Medan, a thrift clothing store. A quantitative approach was used, involving a survey of 100 respondents. Validity and reliability tests confirmed the data’s accuracy. Multiple linear regression analysis with SPSS 26 was conducted to analyze the data. The F-test results showed that product quality, price, and promotion simultaneously have a significant impact on purchase decisions (p < 0.05). Partial t-tests revealed that each variable positively and significantly influences purchase decisions, with p-values below 0.05 and t-values exceeding the critical value. The findings suggest that improving product quality, competitive pricing, and effective promotion—especially through social media—are crucial for influencing consumer purchasing behavior at Noah Fashion. This study provides practical insights for thrift store marketers to enhance their marketing strategies.